Do bound structures brake cosmic acceleration? - Schrempp, Lily; Brown, Iain A. (Journal of cosmology and astroparticle physics, 2010)
In this paper we investigate the impact of the coupling between a quintessence field and clustered matter on the average equation of state of the scalar field. We take the NFW profile to be characteristic of bound structures on galactic and cluster scales, and the isothermal distribution to hold for objects on supercluster scales. Solving analytically for the scalar-field profile, we find that the greatest impact on the equation of state comes from the superclusters. Employing numerical case studies, we verify this effect and probe its dependence on the evolutionary state of the supercluster. An estimate across the Hubble volume yields corrections to the homogeneous equation of state of ∼ 3%, increasing with coupling strength.